EFISIENSI BIAYA PRODUKSI PUPUK ORGANIK BERBAHAN DASAR LIMBAH MEDIA BUDIDAYA LALAT TENTARA HITAM (Hermetia illucens) - Nurul Risti Mutiarasari; Yogi Nirwanto (Universitas Galuh, 2022)
Availability of organic waste has attracted the community as a business opportunity to utilize organic waste. One of the uses of organic waste that is carried out is as a growing medium and feed in the cultivation of black soldier fly (BSF) or maggot feed which at the end of the period there is residual cultivation media in the form of organic material that has the potential to be used as organic fertilizer. Organic fertilizer is an alternative to the use of organic waste that can be produced from the rest of the black army fly (BSF) cultivation media. The purpose of this study was to measure the cost of production and the level of efficiency of production costs of organic fertilizer based on residual BSF cultivation media using R/C ratio analysis. The research method used is a case study on community groups in Cipedes District, Tasikmalaya City since 2018. The results showed that the cost of production of the remaining BSF cultivation media is Rp. 14,663.00 and the results of the R/C ratio analysis are 1.40, indicated that the used of costs in the production process of organic fertilizer from waste of BSF cultivation media is efficient.